School tobacco-related curriculum and behavioral factors associated with cigarette smoking among school-going adolescents in Zambia: Results from the 2011 GYTS study - Cosmas Zyambo; Pawel Olowski; David Mulenga; Franklin Liamba; Paul Syapiila; Seter Siziya (Tobacco Induced Diseases, 2022)
Introduction Tobacco smoking is a global public health concern. It has been projected that children and young people who are alive today in developing countries will bear the most burden of tobacco-related morbidity and mortality in the near future. This study investigated the school tobacco-related curriculum and behavioral factors associated with cigarette smoking among school-going adolescents.